Morphogenesis in pastures with Tanzania grass fertilized with nitrogen doses under a grazing system - Cecilio Viega Soares Filho; Ulysses Cecato; Ossival Lolato Ribeiro; Claudio Fabrício da Cruz Roma; Tatiane Beloni (Acta Scientiarum. Animal Sciences, 2015)
The morphogenetic and structural characteristics, coupled to forage production of Tanzania grass with nitrogen (N) doses during the seasons of the year, at intermittent grazing, were analyzed. The experimental design consisted of a totally randomized block with split plots and four replications. The plots comprised 0, 150, 300 and 450 kg ha-1 N levels, whereas the sub-plots were the seasons. Urea was applied three times on the pasture and had a positive effect on the rates of leaf elongation and emergence and on the number of live leaves of Tanzania grass in the spring and summer. High nitrogen fertilization associated with shorter grazing intervals triggered a higher percentage of leaf blades in the management of Tanzania grass under rotational stocking at a height of 70 cm on the admittance of animals for grazing and their exit at 30 cm stubble height.